Respuesta :

Answer:

see explanation

Step-by-step explanation:

the standard form of a quadratic expression is ax² + bx + c ( a ≠ 0 )

(1)

(2x + 5)(x + 1)

each term in the second factor is multiplied by each term in the first factor, that is

2x(x + 1) + 5(x + 1) ← distribute parenthesis

= 2x² + 2x + 5x + 5 ← collect like terms

= 2x² + 7x + 5 ← in standard form (a = 2, b = 7, c = 5 )

(2)

(x - 2)(x + 2)

= x(x + 2) - 2(x + 2) ← distribute parenthesis

= x² + 2x - 2x - 4 ← collect like terms

= x² - 4 ← in standard form (a = 1, b = 0, c = - 4 )

ACCESS MORE